On dom: the case for revisiting domicile law reform in the United Kingdom and Australia. (3rd July 2021) - Paterson, Matthew
ABSTRACT: Domicile is an old and unwieldy concept of private international law. Nevertheless, it remains relevant to a variety of areas of law across the UK and Australia. While neither country has codified the law of domicile, Australia has gone much further to modernise it. This paper discusses the state of the law of domicile in the United Kingdom and Australia and the effect of Australia's modernisation attempts. After addressing the state of the law as it currently stands, it shows how both the subjective nature of domicile's focus on a person's intention, and more mechanical rules in respect of domiciles of dependence, are outmoded and in serious need of reform.